Quantitative detection of pepper powder adulterated with rice powder using Fourier-transform near infrared spectroscopy - R Lapcharoensuk; S Chalachai; S Sinjaru; P Singsriand; J Hongwiangjan; N Yaemphochai (My University, 2019)
Abstract Near infrared (NIR) spectroscopy model was developed for detecting pepper powder adulterated with rice powder. The adulterated pepper powder samples were prepared by mixing rice powders with pure pepper powder to 19 levels of concentrations (w/w) from 5-95%w/w. Two hundred ten NIR spectra of pure and adulterant pepper powders were recorded using Fourier-transform near infrared spectrometer. The NIRs quantitative model for detecting adulterant pepper were established using partial least squares regression (PLS). The optimum model was established from NIR spectra treated by constant offset elimination with the R v a l 2 of 0.99. These results show that the NIR spectroscopy could be a modern method for monitoring adulteration of pepper powder with rice powder.
Keywords: Fourier transform spectroscopy; Essential Oils and Antimicrobial Activity